Opportunities and Threats Based on Budget Laws and Strategies for Enhancing the Banking Performance of the Cooperative Development Bank - Ehteshamnejad, Ehsan; Pakzad, Mahdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective:  The objective of this study is to explore the opportunities and threats posed by budget laws on the banking performance of the Tose’e Ta’avon Bank and to propose strategies for enhancing its performance. This research aims to provide a comprehensive understanding of how budget provisions from 2018 to 2023 impact the bank's operations, financial stability, and risk management practices.Methodology: This study employs a qualitative research methodology, combining content analysis of budget laws, financial statements, and expert consultations. The content analysis focuses on budget laws from 2018 to 2023, identifying key provisions that impact the Tose’e Ta’avon Bank’s performance. Financial statements of the bank are analyzed to assess the financial implications of these provisions. Expert consultations with banking professionals and policymakers provide insights into the practical challenges and opportunities associated with these budget laws.Findings: The study identifies several significant opportunities for the Tose’e Ta’avon Bank, including the ability to sell surplus assets, invest in strategic national projects, and issue bonds with government guarantees. These provisions can enhance the bank's financial stability and growth potential. Conversely, the study also identifies significant threats, such as increased financial obligations and regulatory constraints, which can strain the bank's financial resources and impact liquidity. Effective risk management and strategic utilization of opportunities are critical to navigating these challenges.Conclusion: Budget laws present both substantial opportunities and significant threats to the Tose’e Ta’avon Bank. While opportunities like asset sales and strategic investments can enhance financial stability, threats from extended debt repayment periods and stringent financial requirements necessitate robust risk management practices. The study underscores the importance of a balanced approach to budget policy formulation, emphasizing the need for effective governance, proactive risk management, and collaborative dialogue with policymakers to optimize the bank's performance and contribute to broader economic development goals.